CERVICAL SCREENING: DO GYNECOLOGISTS THEMSELVES PRACTICE WHAT THEY PREACH? A STUDY BASED IN TERTIARY CARE HOSPITALS OF LAHORE: Cervical screening: Practice What They Preach? - Nawaz, Qudsia; Akhtar, Shamim; Zafar, Mona; Arif, Ayesha; Arif, Sadia; Mushtaq, Qurrat- ul-Ain (Pakistan Armed Forces Medical Journal, 2015)
Objectives: To determine the frequency of self-compliance to cervical screening guidance among the sexually active female gynecologists in tertiary care hospitals. To identify the possible barriers to effective screening in those who do not undergo cervical screening. Study Design: Cross sectional study. Place and Duration of Study: This study was conducted in the Obstetrics & Gynecology department of various tertiary care hospitals of Lahore* from 1st Jun 2012 to 30th Nov 2012. Patients and Methods: Total 157 female gynecologists, serving in various positions in tertiary care hospitals of Lahore were interviewed by using a structured self reporting performa. The performa was designed to find out the number of gynecologists undergoing pap screening, and in those who fail to undergo screening the single most important barrier presumed to be preventing them from undergoing screening was also evaluated. Results: In this study, only 3.1% of the subject population was found to be undergoing pap-screening, which reflects the national level of screening in urban areas, in sharp contrast to the studies being conducted in developed countries, with screening coverage rates of more than 80%. Conclusion: The prevalence of pap screening in the subject population is disappointingly low and drastic steps are needed to bring about a change in attitude of the subject population which cannot be brought about without changing the current culture of self-negligence and least prioritization for self, in the feminine part of our society.